Computer and computing technologies in agriculture X : 10th IFIP WG 5.14 International Conference, CCTA 2016, Dongying, China, October 19-21, 2016, Proceedings /: 10th IFIP WG 5.14 International Conference, CCTA 2016, Dongying, China, October 19-21, 2016, Proceedings. (2019) - Unknown
No abstract available